Pelatihan Penerapan Alsintan Sebagai Upaya Peningkatan Sumber Daya Kelompok Tani Di Desa Palrejo Jombang - Suesthi Rahayuningsih; Achmad Rijanto; Dicki Nizar Zulfika (CV. Multi Kreasi Media, 2026)
Agricultural machinery application training was part of the Student Community Service Program from the Ministry of Higher Education, Science and Technology. This community service activity was partnered with the Farmers Group in Palrejo Village, Sumobito District, Jombang Regency, East Java Province. The Problems of the Palrejo Farmers Group in the production aspect was that farmers' income was not optimal due to high labor costs during rice planting and the large use of water pump fuel during the dry season. Meanwhile, from the management aspect, the farmer group did not yet have assets in the form of fuel-efficient rice planting machines or rice field water pumps. The solution to overcome the problems of Poktan Palrejo was that the implementation team donated three units of rice planting machines (rice transplanters) to reduce labor costs, and one unit of a water pump machine fueled by Liquefied Petroleum Gas (LPG), which was more fuel-efficient during the dry season. Training on the use of both machines was also provided. This service method consisted of the provision or grant of agricultural machinery assets and training in their application. The results achieved from this community service activity were that the Farmer Group had three units of rice planting machines, one unit of an LPG-fueled rice field water pump, and increased resources in the form of skills to use these two tools.